Beta slashed generalised half-normal distribution - Kanfer, Frans; Millard, Sollie (South African Statistical Journal, 2017)
In this paper we propose the beta slashed generalised half-normal distribution, which includes some important distributions such as the half-normal, slashed half-normal and generalised slashed half-normal distributions. Explicit expressions for the cumulative distribution and characteristic functions are derived. The maximum likelihood estimates of the parameters are obtained via the EM algorithm and the value of the proposed model is illustrated with an application on fatigue data.